Quitosana funcionalizada com líquidos iônicos para adsorção de corantes - Vieira, Jean Carlos Bauer (2024)
This work presents the synthesis and characterization of chitosan derivatives containing imidazolium groups in their structure. The characterization was carried out using nuclear magnetic resonance (NMR), infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) techniques. The derivatives obtained were called Polymer A and Polymer B. Hydrogels were obtained from both compounds, varying the preparation method. These hydrogels were characterized through rheological analyses, measuring the storage (G’) and loss (G’’) moduli, in addition to viscosity. Scanning electron microscopy (SEM) images of the hydrogels were also obtained. The results indicated the occurrence of hydrogel formation, since G’ > G’’ was observed in the frequency range used. Viscosity analysis demonstrated the pseudoplastic behavior of the hydrogels. It is assumed that the formation of hydrogels occurred through the physical cross-linking of polymer chains. The results also indicated that the hydrogels formed can be classified as weak according to the G' values and the profile of the curves, especially in the case of the Polymer B hydrogel. Furthermore, Polymer B was used in the adsorption of the dye Acid Orange 7 (AO7) from aqueous solutions. Due to the solubility of Polymer B in water, it was cross-linked with chitosan and glutaraldehyde (Quit-PolB). AO7 adsorption tests were carried out using three other compounds for comparison: pure chitosan (Quit), chitosan cross-linked with tripolyphosphate (Quit-TPP) and chitosan cross-linked with a poly(ionic liquid) forming a semi-interpenetrating polymer network (sIPN). These adsorbents were characterized using the techniques mentioned above, in addition to analysis using BET isotherms, mercury intrusion porosimetry and SEM. Several parameters were varied in the adsorption experiments, measuring the efficiency and adsorption capacity (q) values. The adsorption capacity of adsorbents containing groups derived from ionic liquids (Quit-PolB and sIPN) proved to be resistant to pH changes. The Quit-PolB adsorbent demonstrated less impact with variation in the ionic strength of the medium. The same adsorbent presented a qmax of 292 mg g-1, being the highest value among the adsorbents used and a high value compared to the literature. Kinetic analyzes demonstrated that most adsorbents follow a pseudo-first order profile. It is assumed that the main adsorption mechanism involves the electrostatic interaction between the positively charged polymer and the anionic dye, with the Quit-PolB adsorbent showing additional interactions. Studies on dye desorption from adsorbents and reuse of adsorbents in new dye capture and release cycles were carried out.